Surviving Coral Bleaching Events: Porites Growth Anomalies on the Great Barrier Reef - Cantin, Neal E.; Lough, Janice M. (PLOS ONE, 2014)
Mass coral bleaching affected large parts of the Great Barrier Reef (GBR) in 1998 and 2002. In this study, we assessed if signatures of these major thermal stress events were recorded in the growth characteristics of massive Porites colonies. In 2005 a suite of short (<50 cm) cores were collected from apparently healthy, surviving Porites colonies, from reefs in the central GBR (18–19°S) that have documented observations of widespread bleaching. Sites included inshore (Nelly Bay, Pandora Reef), annually affected by freshwater flood events, midshelf (Rib Reef), only occasionally affected by freshwater floods and offshore (Myrmidon Reef) locations primarily exposed to open ocean conditions. Annual growth characteristics (extension, density and calcification) were measured in 144 cores from 79 coral colonies and analysed over the common 24-year period, 1980–2003. Visual examination of the annual density bands revealed growth hiatuses associated with the bleaching years in the form of abrupt decreases in annual linear extension rates, high density stress bands and partial mortality. The 1998 mass-bleaching event reduced Porites calcification by 13 and 18% on the two inshore locations for 4 years, followed by recovery to baseline calcification rates in 2002. Evidence of partial mortality was apparent in 10% of the offshore colonies in 2002; however no significant effects of the bleaching events were evident in the calcification rates at the mid shelf and offshore sites. These results highlight the spatial variation of mass bleaching events and that all reef locations within the GBR were not equally stressed by the 1998 and 2002 mass bleaching events, as some models tend to suggest, which enabled recovery of calcification on the GBR within 4 years. The dynamics in annual calcification rates and recovery displayed here should be used to improve model outputs that project how coral calcification will respond to ongoing warming of the tropical oceans.